HbA2 levels in normal adults are influenced by two distinct genetic mechanisms. (9th October 2012) - Menzel, Stephan; Garner, Chad; Rooks, Helen; Spector, Tim D.; Thein, Swee Lay
Summary Using a genome‐wide association study, we found that common inter‐individual differences in haemoglobin A2 (HbA2, α2δ2) levels are largely governed by genetic factors (42% of variability). The influence of age (1%) and sex (4%) was small. HbA2 levels were influenced by two loci: the HBS1L‐MYB locus on chromosome 6q, which has been shown to have pleiotropic effects on other haematological traits; and a second locus surrounding HBB, the gene encoding β‐globin. Our results suggest that HbA2 levels in adults are influenced by two different biological processes: one via kinetics of erythropoiesis, and the other, via competition between HBB and HBD activity.